The Influence of Ship Charter Service Quality and Marketing Strategy on Experience That Implications Customer Satisfaction at PT. Citra Maritime Jakarta - Eko Andi Mulyadi; Dicky Hadi Saputra; April Gunawan Malau; Marihot Simanjuntak (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to analyze the effect of Charter Ship Service Quality and Marketing Strategy on Customer Experience that impacts Customer Satisfaction at PT. Citra Maritime Jakarta. The main issue addressed in this study is how the quality of services provided and the marketing strategies implemented can influence customer experience and satisfaction. This research adopts a quantitative approach with an explanatory research design. The population of this study consists of customers who use charter ship services at PT. Citra Maritime Jakarta, with a sample size of 100 respondents selected through purposive sampling. Primary data was obtained through the distribution of questionnaires measuring respondents' perceptions of service quality, marketing strategy, customer experience, and customer satisfaction. Data analysis was conducted using Structural Equation Modeling (SEM) methods. The results show that charter ship service quality and marketing strategy have a positive and significant effect on customer experience. Furthermore, customer experience was found to have a positive impact on customer satisfaction. These findings emphasize the importance of improving service quality and implementing sustainable marketing strategies to enhance customer experience and satisfaction. This study provides practical contributions to the development of marketing strategies and the improvement of service quality in the charter ship service sector.